Composite material, semiconductor package, and method for manufacturing the composite material
The composite material with alternating copper and molybdenum layers addresses crack issues in heat sinks by maintaining low expansion and high conductivity through controlled residual stress, ensuring durability and efficiency.
Patent Information
- Application Number
- JP2022571545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-24
- Filing Date
- 2021-12-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-12-22
AI Technical Summary
Existing heat sinks with copper and copper-molybdenum layers experience cracks due to thermal expansion during brazing, leading to increased linear expansion coefficients.
A composite material with alternating copper and molybdenum powder compact layers, impregnated with copper, maintains low compressive residual stress, preventing significant deformation and crack formation during brazing.
The composite material maintains a low linear expansion coefficient and high thermal conductivity even after brazing, reducing crack occurrence and temperature differences.
Smart Images

Figure 0007658992000003 
Figure 0007658992000004 
Figure 0007658992000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite material, a semiconductor package, and a method for manufacturing the composite material. This application claims priority to Japanese Patent Application No. 2020-214612, filed on December 24, 2020. All contents of the Japanese patent application are incorporated herein by reference. [Background technology]
[0002] Patent Document 1 (JP 2019-96654 A) describes a heat sink. The heat sink described in Patent Document 1 has a first surface and a second surface. The second surface is the opposite surface of the first surface. The heat sink described in Patent Document 1 has a plurality of copper layers and a plurality of copper-molybdenum layers. The copper layers and the copper-molybdenum layers are alternately laminated along the thickness direction of the heat sink so that the copper layers are located on the first surface and the second surface of the heat sink. The heat sink described in Patent Document 1 is joined to a package member by brazing. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-96654 A Summary of the Invention
[0004] The composite material of the present disclosure is plate-shaped and has a first surface and a second surface. The second surface is the opposite surface of the first surface. The composite material includes a plurality of first layers and at least one second layer. The first layers and the second layers are alternately laminated along the thickness direction of the composite material such that the first layers are located on the first surface and the second surface. The first layer is a layer containing copper. The second layer is a layer of a molybdenum powder compact impregnated with copper. A compressive residual stress of 50 MPa or less acts on the first layer located on the first surface and the first layer located on the second surface. [Brief description of the drawings]
[0005] [Figure 1] FIG. 1 is a perspective view of a composite material 10. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II of FIG. [Figure 3A] FIG. 3A is a first explanatory diagram of the procedure for producing a sample for measuring the thermal conductivity of the composite material 10 in the thickness direction. [Figure 3B] FIG. 3B is a second explanatory diagram of the procedure for producing a sample for measuring thermal conductivity in the thickness direction of the composite material 10. [Figure 3C] FIG. 3C is a third explanatory diagram of the procedure for producing a sample for measuring thermal conductivity in the thickness direction of the composite material 10. [Figure 4] FIG. 4 is an explanatory diagram of a method for evaluating the heat dissipation performance of the composite material 10. As shown in FIG. [Diagram 5] FIG. 5 is a manufacturing process diagram of the composite material 10. [Figure 6] FIG. 6 is a cross-sectional view of an example of a laminate 20. As shown in FIG. [Figure 7] FIG. 7 is an exploded perspective view of the semiconductor package 100. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] [Problem that this disclosure aims to solve] According to the findings of the present inventors, in the heat sink described in Patent Document 1, cracks are generated between the copper layer and the copper-molybdenum layer due to the heat generated during brazing, which causes the linear expansion coefficient to increase.
[0007] The present disclosure provides a composite material capable of maintaining a low coefficient of linear expansion even after heat is applied for brazing, a semiconductor package using the same, and a method for manufacturing the composite material.
[0008] [Effects of this disclosure] The composite material of the present disclosure can maintain a low coefficient of linear expansion and high thermal conductivity even after heat is applied for brazing.
[0009] [Description of the embodiments of the present disclosure] First, embodiments of the present disclosure will be listed and described.
[0010] (1) A composite material according to an embodiment of the present disclosure is plate-shaped and has a first surface and a second surface. The second surface is the opposite surface of the first surface. The composite material includes a plurality of first layers and at least one second layer. The first layers and the second layers are alternately laminated along the thickness direction of the composite material such that the first layers are located on the first surface and the second surface. The first layer is a layer containing copper. The second layer is a layer of a molybdenum powder compact impregnated with copper. A compressive residual stress of 50 MPa or less acts on the first layer located on the first surface and the first layer located on the second surface.
[0011] In the composite material (1) above, the compressive residual stress acting on the first layer located on the first surface and the first layer located on the second surface is small, so even if the compressive residual stress is released when heat for brazing is applied, the first layer does not deform significantly and cracks are unlikely to occur at the interface between the first layer and the second layer. Therefore, the composite material (1) above can maintain a low linear expansion coefficient even after heat for brazing is applied.
[0012] (2) In the composite material of (1) above, after holding at 800°C for 15 minutes, the composite material may have a linear expansion coefficient in a direction parallel to the first surface and the second surface of 6 ppm / K or more and 10 ppm / K or less when the temperature of the composite material is changed from room temperature to 200°C. After holding at 800°C for 15 minutes, the composite material may have a thermal conductivity in the thickness direction of 230 W / m K or more.
[0013] The composite material of (2) above can maintain a low linear expansion coefficient and high thermal conductivity even after heat is applied for brazing.
[0014] (3) In the composite material of (1) or (2) above, the total number of the first layers and the second layers may be 5 or more. After being held at 800°C for 15 minutes, the thermal conductivity of the composite material in the thickness direction may be 261 W / m K or more.
[0015] The composite material of (3) above can maintain a higher thermal conductivity even after the heat for brazing is applied.
[0016] (4) In the composite materials of (1) to (3) above, the linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 800°C before being held at 800°C for 15 minutes may be 7.5 ppm / K or more and 8.5 ppm / K or less.
[0017] According to the composite material of (4) above, when a case component is brazed to the composite material, it is possible to suppress the occurrence of cracks in the brazing material due to the difference between the linear expansion coefficient of the composite material and the linear expansion coefficient of the case component.
[0018] (5) In the composite material of (1) to (4) above, the thickness of the first layer located on the first surface and the thickness of the first layer located on the second surface may be 25 percent or less of the thickness of the composite material. The thickness of the second layer may be more than 10 percent of the thickness of the composite material. The volume ratio of molybdenum in the second layer may be 55 percent or more. The volume ratio of molybdenum in the composite material may be more than 13 percent and less than 43 percent.
[0019] (6) In the composite material of (1) to (5) above, the volume of copper in the first layer located on the first surface ratio A volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface may be 90 percent or more. A thickness of the first layer located on the first surface and a thickness of the first layer located on the second surface may be 15 percent or more of a thickness of the composite material.
[0020] In the composite material of (6) above, the temperature difference between the center of the first surface (second surface) and the end of the first surface (second surface) can be reduced.
[0021] (7) In the composite material of (1) to (6) above, the thickness of the second layer may be 18 percent or more of the thickness of the composite material. A change in the linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200°C before and after holding at 800°C for 15 minutes may be 0.3 ppm / K or less.
[0022] According to the composite material of (7) above, the deterioration of the linear expansion coefficient caused by the application of heat for brazing can be further suppressed.
[0023] (8) A composite material according to another embodiment of the present disclosure is plate-shaped and has a first surface and a second surface. The second surface is the opposite surface of the first surface. The composite material includes a plurality of first layers and at least one second layer. The first layers and the second layers are alternately laminated along the thickness direction of the composite material such that the first layers are located on the first surface and the second surface. The first layer is a layer containing copper. The second layer is a layer of a molybdenum powder compact impregnated with copper. After being held at 800°C for 15 minutes, the composite material has a linear expansion coefficient of 6 ppm / K or more and 10 ppm / K or less in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200°C. After being held at 800°C for 15 minutes, the composite material has a thermal conductivity of 230 W / m·K or more in the thickness direction.
[0024] The composite material of (8) above can maintain a low linear expansion coefficient and high thermal conductivity even after heat is applied for brazing.
[0025] (9) In the composite material of (8) above, before being held at 800°C for 15 minutes, the linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 800°C may be 7.5 ppm / K or more and 8.5 ppm / K or less.
[0026] According to the composite material of (9) above, when brazing a case member to the composite material, it is possible to suppress the occurrence of cracks in the brazing material due to the difference between the linear expansion coefficient of the composite material and the linear expansion coefficient of the case member.
[0027] (10) In the composite material of (8) or (9) above, the total number of the first layers and the second layers may be equal to or greater than 5. After being held at 800°C for 15 minutes, the composite material may have a thermal conductivity in a thickness direction of 261 W / m K or greater.
[0028] According to the composite material of (10) above, even after heat for brazing is applied, a higher thermal conductivity can be maintained.
[0029] (11) In the composite material of (8) to (10) above, the thickness of the first layer located on the first surface and the thickness of the first layer located on the second surface may be 25 percent or less of the thickness of the composite material. The thickness of the second layer may be more than 10 percent of the thickness of the composite material. The volume ratio of molybdenum in the second layer may be 55 percent or more. The volume ratio of molybdenum in the composite material may be more than 13 percent and less than 43 percent.
[0030] (12) In the composite material of (8) to (11) above, the volume of copper in the first layer located on the first surface ratio A volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface may be 90 percent or more. A thickness of the first layer located on the first surface and a thickness of the first layer located on the second surface may be 15 percent or more of a thickness of the composite material.
[0031] In the composite material of (12) above, the temperature difference between the center of the first surface (second surface) and the end of the first surface (second surface) can be reduced.
[0032] (13) In the composite material according to any one of (8) to (12) above, the thickness of the second layer may be 18 percent or more of the thickness of the composite material. A change in the linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200° C. before and after holding at 800° C. for 15 minutes may be 0.3 ppm / K or less.
[0033] According to the composite material of (13) above, the deterioration of the linear expansion coefficient caused by the application of heat for brazing can be further suppressed.
[0034] (14) A semiconductor package according to an embodiment of the present disclosure includes a plate-shaped composite material having a first surface and a second surface opposite to the first surface, and a case member brazed to either the first surface or the second surface. The composite material has a plurality of first layers and at least one second layer. The first layers and the second layers are alternately laminated along the thickness direction of the composite material such that the first layers are located on the first surface and the second surface. The first layer is a layer containing copper. The second layer is a layer of a molybdenum powder compact impregnated with copper. The linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200°C is 6 ppm / K or more and 10 ppm / K or less. The thermal conductivity of the composite material in the thickness direction is 230 W / m·K or more.
[0035] According to the semiconductor package of (14) above, the low linear expansion coefficient and high thermal conductivity of the composite material can be maintained even after heat is applied during brazing.
[0036] (15) In the semiconductor package of (14) above, the total number of the first layers and the second layers may be equal to or greater than 5. After being held at 800°C for 15 minutes, the thermal conductivity of the composite material in a thickness direction may be equal to or greater than 261 W / m K.
[0037] According to the semiconductor package of (15) above, the high thermal conductivity of the composite material can be maintained even after the heat for brazing is applied.
[0038] (16) In the semiconductor package of (14) or (15) above, the thickness of the first layer located on the first surface and the thickness of the first layer located on the second surface may be 25 percent or less of the thickness of the composite material. The thickness of the second layer may be more than 10 percent of the thickness of the composite material. The volume ratio of molybdenum in the second layer may be 55 percent or more. The volume ratio of molybdenum in the composite material may be more than 13 percent and less than 43 percent.
[0039] (17) In the semiconductor package according to (14) to (16) above, the volume of copper in the first layer located on the first surface ratio A volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface may be 90 percent or more. A thickness of the first layer located on the first surface and a thickness of the first layer located on the second surface may be 15 percent or more of a thickness of the composite material.
[0040] According to the semiconductor package of (17) above, it is possible to reduce the temperature difference between the center of the first surface (second surface) and the end of the first surface (second surface).
[0041] (18) In the composite material according to any one of (14) to (17) above, the thickness of the second layer may be 18 percent or more of the thickness of the composite material. A change in the linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200°C before and after holding at 800°C for 15 minutes may be 0.3 ppm / K or less.
[0042] According to the semiconductor package of (18) above, it is possible to further suppress the deterioration of the linear expansion coefficient of the composite material caused by the application of heat for brazing.
[0043] (19) A method for producing a composite material according to an embodiment of the present disclosure includes the steps of preparing a laminate, heating the laminate, and rolling the heated laminate. The laminate has a first surface and a second surface opposite to the first surface. The laminate has a plurality of first plates and at least one second plate. The first plates and the second plates are alternately arranged along the thickness direction of the laminate such that the first plates are located on the first surface and the second surface. The first plate includes copper. The second plate is a molybdenum powder compact impregnated with copper.
[0044] According to the above-mentioned (19) method for producing a composite material, a composite material can be obtained that can maintain a low linear expansion coefficient even after heat is applied for brazing.
[0045] [Details of the embodiment of the present disclosure] The details of the embodiments of the present disclosure will be described with reference to the drawings. In the following drawings, the same or corresponding parts are designated by the same reference numerals, and redundant description will not be repeated.
[0046] (First embodiment) A composite material according to a first embodiment (hereinafter referred to as "composite material 10") will be described.
[0047] <10 components of composite material> Fig. 1 is a perspective view of a composite material 10. Fig. 2 is a cross-sectional view taken along line II-II in Fig. 1. As shown in Figs. 1 and 2, the composite material 10 is in the form of a plate. The composite material 10 has a first surface 10a and a second surface 10b. The second surface 10b is the opposite surface to the first surface 10a in the thickness direction of the composite material 10.
[0048] The thickness of the composite material 10 is defined as thickness T1. Thickness T1 is the distance between the first surface 10a and the second surface 10b. Hereinafter, the direction perpendicular to the thickness direction of the composite material 10 (the direction parallel to the first surface 10a and the second surface 10b) may be referred to as the intra-layer direction.
[0049] The composite material 10 has a plurality of first layers 11 and at least one second layer 12. The total number of the first layers 11 and the second layers 12 is 3 or more. The first layers 11 and the second layers 12 are alternately laminated along the thickness direction of the composite material 10. From another perspective, the second layer 12 is sandwiched between two first layers 11.
[0050] A first layer 11 is located on the first surface 10a and the second surface 10b. The first layer 11 located on the first surface 10a may be referred to as the first layer 11a, and the first layer 11 located on the second surface 10b may be referred to as the first layer 11b.
[0051] The thickness of the first layer 11 is defined as T2. The thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b are preferably 15 percent or more of the thickness T1. The thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b are, for example, 25 percent or less of the thickness T1.
[0052] The first layer 11 is a layer containing copper. The first layer 11 may contain molybdenum in addition to copper. The volume ratio of copper in the first layer 11 is, for example, 80 percent or more. The volume ratio of copper in the first layer 11 is preferably 90 percent or more. The first layer 11 may be pure copper (the volume ratio of copper in the first layer 11 may be 100 percent).
[0053] The compressive residual stress acting on the first layer 11a and the compressive residual stress acting on the first layer 11b are 50 MPa or less. The compressive residual stress acting on the first layer 11a and the compressive residual stress acting on the first layer 11b are preferably 40 MPa or less. The compressive residual stress acting on the first layer 11a and the compressive residual stress acting on the first layer 11b are measured by X-ray diffraction (more specifically, sin 2 It is measured using the φ method.
[0054] In preparing a sample for measuring the compressive residual stress acting on the first layer 11a (first layer 11b), first, a measurement sample having a width of 1 mm and a length of 5 mm is cut out from the composite material 10. The width direction and length direction of the measurement sample are perpendicular to the thickness direction of the composite material 10.
[0055] Secondly, the 20 measurement samples are arranged on a plane so as to be in contact with each other. At this time, the measurement samples are arranged so that the cross sections parallel to the thickness direction of the composite material 10 face upward. Also, at this time, the measurement samples are arranged so as to form two rows in the length direction of the measurement samples.
[0056] Third, the top surfaces of the aligned measurement samples are polished. This polishing is performed so that the step between the top surfaces of each measurement sample is 0.1 mm or less. The top surfaces of the measurement samples thus prepared are irradiated with X-rays (CuKα rays) to obtain a sin 2 Residual stress is measured using the φ method.
[0057] The second layer 12 is a layer of copper-molybdenum infiltrant. The copper-molybdenum infiltrant is a material in which copper is impregnated into the voids of a molybdenum compact (a product of compressing molybdenum powder) and then rolled. The volume ratio of molybdenum in the second layer 12 is preferably 55 percent or more. The volume ratio of molybdenum in the second layer 12 is, for example, 85 percent or less.
[0058] The thickness of the second layer 12 is designated as thickness T3. It is preferable that thickness T3 exceeds 10 percent of thickness T1. For example, thickness T3 is equal to or less than 35 percent of thickness T1. It is preferable that thickness T3 and the volume ratio of molybdenum in the second layer 12 are set so that the volume ratio of molybdenum in the composite material 10 is greater than 13 percent and less than 43 percent. It is preferable that thickness T3 is equal to or greater than 18 percent and equal to or less than 35 percent of thickness T1.
[0059] After being held at 800°C for 15 minutes, it is preferable that the linear expansion coefficient of composite material 10 in the intralayer direction when the temperature of composite material 10 is changed from 27°C (hereinafter referred to as "room temperature") to 200°C is 6 ppm / K or more and 10 ppm / K or less.
[0060] The linear expansion coefficient in the in-layer direction of the composite material 10 is measured based on the expansion displacement in the in-layer direction of the composite material 10 when the temperature is changed from room temperature to 200°C, taking into consideration the operating temperature of a semiconductor package in which the composite material 10 is used. Also, the linear expansion coefficient in the in-layer direction of the composite material 10 is measured after being held at 800°C for 15 minutes, taking into consideration the heating that occurs when the composite material 10 is brazed.
[0061] Before being held at 800° C. for 15 minutes, the linear expansion coefficient of the composite material 10 in the intralayer direction when the temperature of the composite material 10 is changed from room temperature to 800° C. is preferably 7.5 ppm / K or more and 8.5 ppm / K or less. This is because the case members brazed to the composite material 10 are often made of alumina, and the linear expansion coefficient of alumina when the temperature is changed from room temperature to 800° C. is considered to be about 8 ppm / K.
[0062] It is preferable that the change (increase) in the linear expansion coefficient of composite material 10 in the intralayer direction when the temperature of composite material 10 is changed from room temperature to 200°C before and after holding at 800°C for 15 minutes is 0.3 ppm / K or less.
[0063] The linear expansion coefficient in the in-layer direction of the composite material 10 when the temperature changes from room temperature to 200°C (800°C) is calculated by measuring the expansion displacement in the in-layer direction of the composite material 10 when the temperature changes from room temperature to 200°C (800°C) using a TD5000SA (manufactured by Bruker AXS). When calculating the linear expansion coefficient in the in-layer direction of the composite material 10 when the temperature changes from room temperature to 200°C, the planar shape of the composite material 10 is a rectangle of 3 mm x 15 mm. The measured value is the average value for three samples.
[0064] When the size of the composite material 10 to be evaluated is smaller than 3 mm × 15 mm, the linear expansion coefficient may be calculated using an X-ray diffraction method. 2 The collected heat dissipation surface should be a rectangle with one side measuring approximately 10 mm or more. X-rays are irradiated onto the heat dissipation surface at room temperature and 800°C, and the diffraction angle (2θ) is derived from the diffraction peak corresponding to Cu(331). Using the following formula from this diffraction angle, the rate of change in lattice spacing can be used as the linear expansion coefficient. If anisotropy exists within the material's surface, align the sample so that the direction to be measured for the linear expansion coefficient is parallel to the plane of incidence of the X-rays. The formula for calculating the linear expansion coefficient when room temperature is 25°C is shown below.
[0065] (Linear expansion coefficient) = (1 / sin(θat800℃)-1 / sin(θat25℃)) × sin(θat25℃) / (800-25) Here, θat25°C is 1 / 2 the diffraction angle 2θ when measured at 25°C, and θat800°C is 1 / 2 the diffraction angle 2θ when measured at 800°C.
[0066] After being held at 800°C for 15 minutes, the thermal conductivity of the composite material 10 in the thickness direction is preferably 230 W / m·K or more. More preferably, after being held at 800°C for 15 minutes, the thermal conductivity of the composite material 10 in the thickness direction is 261 W / m·K or more. This thermal conductivity is measured at room temperature. Note that the thermal conductivity of the composite material 10 in the thickness direction is measured after being held at 800°C for 15 minutes in consideration of the heating that occurs during brazing of the composite material 10.
[0067] The thermal conductivity in the thickness direction of the composite material 10 is measured by a laser flash method. More specifically, the thermal diffusion coefficient of the composite material 10 is measured using LFA457MicroFlash (manufactured by NETZSCH), and the thermal conductivity in the thickness direction of the composite material 10 is calculated based on the thermal diffusion coefficient and the volume ratio and specific heat of each of the constituent materials of the composite material 10.
[0068] When calculating the thermal conductivity of the composite material 10 in the thickness direction, the composite material 10 is cut out so that the planar shape is a circle with a diameter of 10 mm. When calculating the thermal conductivity, the specific heat of each of the constituent materials is determined based on "Metal Data Book, 4th Edition" (2004, Maruzen Publishing), edited by the Japan Institute of Metals. Prior to measuring the thermal conductivity of the composite material 10, the thermal conductivity of a pure copper sample of the same shape is measured under the same conditions, and the result is used as a reference to correct the measurement result.
[0069] Fig. 3A is a first explanatory diagram of the procedure for preparing a sample for measuring thermal conductivity in the thickness direction of a composite material 10. As shown in Fig. 3A, a flake 15 is cut out from the composite material 10 to be measured. The thickness, length and width of the flake 15 are t (mm), B (mm) and C (mm), respectively.
[0070] Let X be the number obtained by dividing 2 by t and rounding up the decimal point. Let Y1 be the number obtained by dividing 10 by B and rounding up the decimal point. and The value obtained by dividing 10 by C and rounding up is defined as Y2. From the composite material 10 to be measured, slices 15 in a number equal to the product of X, Y1, and Y2 are cut out.
[0071] FIG. 3B is a second explanatory diagram of the procedure for preparing a sample for measuring the thermal conductivity in the thickness direction of the composite material 10. As shown in FIG. 3B, a block 16 is prepared from X pieces of flakes 15. The thickness, length and width of the block 16 are approximately 2 (mm), B (mm) and C (mm), respectively. In preparing the block 16, first, X pieces of flakes 15 are stacked. At this time, an irregular powder made of pure silver with an average particle size of 4 μm is placed between adjacent flakes 15. The amount of the irregular powder placed between adjacent flakes 15 is 100 mm. 2 The average molecular weight is 0.2g ±30 percent.
[0072] In the production of the block 16, secondly, a rectangular mold (not shown) having an opening with inner dimensions B (mm) x C (mm) is prepared, and the stacked flakes 15 are placed in the opening. The mold is made of graphite. In the production of the block 16, thirdly, the stacked flakes 15 are heat-treated with a load P applied. The load P is 4.9 N or more and 9.8 N or less. The heat treatment is performed in an inert gas atmosphere. The heat treatment is performed at a holding temperature of 900°C and for a holding time of 10 minutes. The heat treatment softens and deforms the amorphous powder, bonding adjacent flakes 15 together, thereby producing the block 16.
[0073] FIG. 3C is a third explanatory diagram of the procedure for preparing a measurement sample for the thermal conductivity in the thickness direction of the composite material 10. As shown in FIG. 3C, a measurement sample 17 having a height of about 10 mm, a width of about 10 mm, and a thickness of about 2 mm is prepared by arranging Y1 blocks 16 vertically and Y2 blocks 16 horizontally. When arranging Y1 blocks 16 vertically and Y2 blocks horizontally, adjacent blocks 16 are bonded to each other with an adhesive member. The adhesive member used is a silver brazing foil, a ceramic adhesive, or the like, which can withstand temperatures up to about 800°C. The blocks 16 arranged vertically and horizontally in Y1 and Y2 rows may be fixed by winding a stainless steel wire or the like around the outer periphery.
[0074] The end temperature difference of the composite material 10 is preferably 50°C or less. FIG. 4 is an explanatory diagram of a method for evaluating the heat dissipation performance of the composite material 10. FIG. 4 shows a schematic view of one side of the composite material 10. The composite material 10 is cut into a rectangular shape having a length and width of 10 mm when viewed from a direction perpendicular to the first surface 10a. A heating element 90 is brought into contact with the center of the first surface 10a of the cut composite material 10. The heating element 90 has a rectangular shape having a length and width of 10 mm when viewed from a direction perpendicular to the first surface 10a. The heating value of the heating element 90 is 50W.
[0075] The aluminum fin 80 is bonded to the second surface 10b of the cut composite material 10 using silicone oil (G-751 manufactured by Shin-Etsu Chemical Co., Ltd.) by applying a load of 9.8 N with the silicone oil placed between the second surface 10b of the cut composite material 10 and the aluminum fin 80.
[0076] The temperature at the interface between the first surface 10a of the cut composite material 10 and the heating element 90 is defined as a first temperature. The temperature at the end (corner) of the first surface 10a of the cut composite material 10 is defined as a second temperature. The temperature at the interface between the second surface 10b of the cut composite material 10 and the aluminum fin 80 is defined as a third temperature. The first temperature, the second temperature, and the third temperature are measured by a thermocouple (not shown). Air cooling of the aluminum fin 80 is controlled so that the third temperature is 25°C±3°C. The ambient temperature as the measurement environment is 25°C±5°C.
[0077] The difference between the first temperature and the second temperature (first temperature - second temperature) when 30 seconds or more have elapsed since the heating element 90 was brought into contact with the first surface 10a of the cut composite material 10 and the temperature has become steady is the end temperature difference of the composite material 10. This end temperature difference is measured 10 times, and the average value is adopted. In other words, the end temperature difference of the composite material 10 is the difference between the temperature at the part of the first surface 10a where the heating element 90 is in contact and the temperature at the end (corner) of the first surface 10a in a state where the heating element 90 is in contact with the first surface 10a and the aluminum fin 80 is bonded to the second surface 10b. The smaller the end temperature difference, the better the thermal conduction in the in-layer direction of the composite material 10.
[0078] <Method of manufacturing composite material 10> Fig. 5 is a manufacturing process diagram of the composite material 10. As shown in Fig. 5, the manufacturing method of the composite material 10 includes a preparation step S1, a heating step S2, and a rolling step S3.
[0079] In the preparation step S1, a laminate 20 is prepared. Fig. 6 is a cross-sectional view of an example of the laminate 20. As shown in Fig. 6, the laminate 20 has a plurality of first plate materials 21 and at least one second plate material 22. The first plate material 21 is formed of the same material as the first layer 11, and the second plate material 22 is formed of the same material as the second layer 12. The first plate materials 21 and the second plate materials 22 are alternately arranged along the thickness direction of the laminate 20.
[0080] The laminate 20 is fixed so that each layer does not move in the direction of a surface perpendicular to the thickness direction by covering the side surfaces with the same material as the first plate material 21. The fixing method is not limited to this method, and the layers may be fixed using a method such as providing through holes and fixing with rivets. Furthermore, the layers may be fixed on top of other plate materials so that they do not move relative to each other.
[0081] In the heating step S2, layer The laminate 20 to which the copper foil is fixed is heated. In this heat treatment, the laminate 20 is heated to a predetermined temperature in a hydrogen atmosphere. This predetermined temperature is a temperature lower than the melting point of copper. This predetermined temperature is, for example, 900°C.
[0082] The rolling step S3 is performed after the heating step S2. In the rolling step S3, the laminate 20 is passed through a rolling roller. As a result, the first plate material 21 and the second plate material 22 are bonded to each other while being rolled, and the composite material 10 having the structure shown in Fig. 1 and Fig. 2 is manufactured. That is, in the composite material 10, the first layer 11 and the second layer 12 are bonded by using a hot roll bonding method.
[0083] <10 Effects of Composite Materials> When a plate-shaped composite material in which layers containing copper (hereinafter referred to as "copper layers") and layers containing molybdenum and copper (hereinafter referred to as "copper molybdenum layers") are alternately laminated is used as a heat spreader for a semiconductor package, a case member is attached to the surface of the composite material by brazing. During this brazing, heating is usually performed at about 800°C for about 15 minutes.
[0084] In the above composite material, the copper layer and the copper molybdenum layer are usually bonded to each other by a diffusion bonding method. As a result, a large compressive residual stress acts on the copper layer. The copper layer is softened by heating during the above brazing. As the copper layer softens, the compressive residual stress acting on the copper layer is released, and the copper layer is significantly deformed, and cracks are generated at the bonding interface with the copper molybdenum layer. These cracks increase the linear expansion coefficient of the above composite material in the in-layer direction.
[0085] In the composite material 10, the first layer 11 and the second layer 12 are bonded by hot roll bonding. During bonding by hot roll bonding, the first layer 11 is cooled while maintaining a higher temperature than the second layer 12 due to the fact that the thermal conductivity of copper is greater than that of molybdenum, and therefore distortion is less likely to remain near the interface with the second layer 12.
[0086] Therefore, in the composite material 10, after the case members are brazed, the occurrence of cracks at the bonding interface between the first layer 11 and the second layer 12 is suppressed. That is, according to the composite material 10, even after the case members are brazed, the linear expansion coefficient in the intralayer direction is maintained low.
[0087] After being held at 800°C for 15 minutes, if the linear expansion coefficient of composite material 10 in the intralayer direction is 6 ppm / K or more and 10 ppm / K or less when the temperature of composite material 10 is changed from room temperature to 200°C and the thermal conductivity of composite material 10 in the thickness direction is 230 W / m·K or more (preferably 261 W / m·K or more), then even after the case components are brazed, the linear expansion coefficient of composite material 10 in the intralayer direction can be reduced while maintaining the thermal conductivity of composite material 10 in the thickness direction.
[0088] When the thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b are 15 percent or more of the thickness T1, and the volume ratio of copper in the first layer 11a and the volume ratio of copper in the first layer 11b are 90 percent or more, heat is likely to diffuse along the in-layer direction on the first surface 10a side and the second surface 10b side. Therefore, in this case, the end temperature difference can be reduced.
[0089] Molybdenum has a smaller linear expansion coefficient and a smaller thermal conductivity than copper. Therefore, the larger the volume ratio of molybdenum in the composite material 10, the smaller the linear expansion coefficient in the in-layer direction of the composite material 10, and the smaller the thermal conductivity in the thickness direction of the composite material 10. The larger the thickness T3, the smaller the thermal conductivity in the thickness direction of the composite material 10, and the smaller the linear expansion coefficient in the in-layer direction of the composite material 10. The larger the volume ratio of molybdenum in the second layer 12, the smaller the thermal conductivity in the thickness direction of the composite material 10, and the smaller the linear expansion coefficient in the in-layer direction of the composite material 10.
[0090] Copper has a larger linear expansion coefficient and a larger thermal conductivity than molybdenum, so that as the thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b increase, the linear expansion coefficient in the in-layer direction of the composite material 10 increases, and the thermal conductivity in the thickness direction of the composite material 10 increases.
[0091] As a result of intensive investigations by the present inventors, it has been found that the volume ratio of molybdenum is more than 13% and less than 43%, the thickness T3 is more than 10% of the thickness T1, the volume ratio of molybdenum in the second layer 12 is 55% or more, and the thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b are smaller than the thickness T1 of the first layer 11a. is thickness T1 When the ratio is 25 percent or less, even after the case components are brazed, the thermal conductivity of the composite material 10 in the thickness direction can be maintained, while the linear expansion coefficient of the composite material 10 in the intralayer direction can be reduced.
[0092] <Example> Samples 1 to 37 were prepared as composite material samples. Samples 1 to 37 are composite materials having the structure shown in FIG. 2. In Samples 1 to 30, the first layer 11 and the second layer 12 are bonded using a hot roll bonding method. In Samples 31 to 37, the first layer 11 and the second layer 12 are bonded using a spark plasma sintering (SPS) method. The SPS method is a method of simultaneously applying Joule heating by current and pressure by a press mechanism to bond the interface of a workpiece such as a metal at an atomic level, and can sinter and densify powder materials and metal bond (diffusion bond) different materials. In this embodiment, the latter effect is utilized. When the SPS method is used, the laminate 20 is placed in a cylindrical graphite mold, and the laminate 20 is heated and pressurized to a predetermined temperature while pulse current is applied. This predetermined temperature is a temperature lower than the melting point of copper. This predetermined temperature is, for example, 900°C. The pressure applied is determined so that the relative density of the composite material is 99 volume percent or more while maintaining the durability of the graphite mold. If this cannot be achieved at the specified temperature, it can be adjusted by increasing the temperature appropriately.
[0093] Table 1 shows the thickness T2 of the first layer 11a and the first layer 11b, the volume ratio of copper in the first layer 11a and the first layer 11b, the thickness T3 of the second layer 12, the volume ratio of molybdenum in the second layer 12, the number of layers, and the compressive residual stress acting on the first layer 11a and the first layer 11b in Samples 1 to 37.
[0094] Although not shown in Table 1, thickness T1 is 1 mm in all samples 1 to 37. In addition, the volume ratio of copper in the first layers 11 other than the first layers 11a and 11b is 100 percent in all samples 1 to 37. In addition, thickness T2 of the first layers 11 other than the first layers 11a and 11b is not shown in Table 1 because it is automatically determined from thicknesses T2 of the first layers 11a and 11b, thickness T3 of the second layer 12, the number of layers, and thickness T1.
[0095] [Table 1]
[0096] The compressive residual stress acting on the first layer 11a and the first layer 11b being 50 MPa or less is defined as condition A. Samples 1 to 30 satisfied condition A, but samples 31 to 37 did not.
[0097] The thickness T2 of the first layer 11a and the first layer 11b being 25 percent or less of the thickness T1 is defined as condition B. The volume ratio of molybdenum in the composite material being more than 13 percent and less than 43 percent is defined as condition C.
[0098] The condition D is that the thickness T3 of the second layer 12 exceeds 10 percent of the thickness T1. The condition E is that the volume ratio of molybdenum in the second layer 12 is 55 percent or more.
[0099] Samples 3 to 14, Samples 18 to 24, and Samples 26 to 29 further satisfied Condition B, Condition C, Condition D, and Condition E. On the other hand, Samples 1 to 2, Samples 15 to 17, Sample 25, and Sample 30 did not satisfy at least one of Condition B, Condition C, Condition D, and Condition E.
[0100] The volume ratio of copper in the first layers 11a and 11b being 90 percent or more is defined as condition F. The thickness T2 of the first layers 11a and 11b being 15 percent or more of the thickness T1 is defined as condition G.
[0101] Samples 3 to 12, Samples 18 to 23, and Samples 26 to 28 further satisfied Conditions F and G. On the other hand, Samples 13 to 14, Sample 24, and Sample 29 did not satisfy at least one of Conditions F and G.
[0102] Number of first layers 11 and number of second layers 12 Sum of Condition H is that thickness T1 is 5 or more and thickness T3 is 18 percent or more of thickness T1. Samples 3 to 11 and Samples 18 to 19 further satisfied condition H. On the other hand, Sample 12, Samples 20 to 23, and Samples 26 to 28 did not satisfy condition H.
[0103] Table 2 shows the results of measuring the linear expansion coefficient in the in-layer direction, the thermal conductivity in the thickness direction, and the end temperature difference for Sample 1 to Sample 37. The linear expansion coefficient was measured as follows: the linear expansion coefficient in the in-layer direction when the temperature was changed from room temperature to 200°C after holding at 800°C for 15 minutes ("first linear expansion coefficient" in Table 2); the linear expansion coefficient in the in-layer direction when the temperature was changed from room temperature to 200°C before holding at 800°C for 15 minutes ("second linear expansion coefficient" in Table 2); and the linear expansion coefficient in the in-layer direction when the temperature was changed from room temperature to 800°C before holding at 800°C for 15 minutes ("third linear expansion coefficient" in Table 2). The thermal conductivity was measured after holding at 800°C for 15 minutes.
[0104] [Table 2]
[0105] The first linear expansion coefficients of Samples 31 to 37 were larger than the first linear expansion coefficients of Samples 1 to 30. As described above, Samples 1 to 30 satisfied Condition A, while Samples 31 to 37 did not satisfy Condition A.
[0106] This comparison reveals that by keeping the compressive residual stress acting on the first layer 11a and the first layer 11b at 50 MPa or less, the occurrence of cracks at the bonding interface between the first layer 11 and the second layer 12 when heat for brazing is applied is suppressed (a low linear expansion coefficient is maintained even after heat for brazing is applied).
[0107] Samples 3 to 14, Samples 18 to 24, and Samples 26 to 29 have a first linear expansion coefficient of 6 ppm / K or more and 10 ppm / K or less. Thickness As described above, Samples 3 to 14, Samples 18 to 24, and Samples 26 to 29 further satisfied Condition B, Condition C, Condition D, and Condition E.
[0108] From this comparison, the volume ratio of molybdenum is more than 13 percent and less than 43 percent, the thickness T3 is more than 10 percent of the thickness T1, and the thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b are is thickness T1 It has been revealed that by having a volume ratio of molybdenum in the second layer 12 be 25 percent or less and a volume ratio of molybdenum in the second layer 12 be 55 percent or more, it is possible to reduce the linear expansion coefficient in the intra-layer direction of the composite material 10 while maintaining the thermal conductivity in the thickness direction of the composite material 10 even after the heat for brazing is applied.
[0109] The third linear expansion coefficients of Samples 3 to 14, Samples 18 to 24, and Samples 26 to 29 were 7.5 ppm / K or more and 8.5 ppm / K or less. 24 and sample 26 29 further satisfied conditions B, C, D and E.
[0110] From this comparison, the volume ratio of molybdenum is more than 13 percent and less than 43 percent, the thickness T3 is more than 10 percent of the thickness T1, and the thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b are is thickness T1 It has been revealed that by having a volume ratio of molybdenum in the second layer 12 be 25 percent or less and a volume ratio of molybdenum in the second layer 12 be 55 percent or more, it is possible to suppress the occurrence of cracks in the brazing material due to the difference between the linear expansion coefficient of the composite material 10 and the linear expansion coefficient of the case components.
[0111] The end temperature differences from Sample 3 to Sample 12, Sample 18 to Sample 23, and Sample 26 to Sample 28 were less than 50° C. As described above, Sample 3 to Sample 12, Sample 18 to Sample 23, and Sample 26 to Sample 28 further satisfied Condition F and Condition G.
[0112] This comparison reveals that the end temperature difference can be reduced by having the thickness T2 of the first layer 11a and the thickness T2 of the first layer 11b be 15 percent or more of the thickness T1, and by having the volume ratio of copper in the first layer 11a and the volume ratio of copper in the first layer 11b be 90 percent or more.
[0113] The difference between the first and second linear expansion coefficients in Samples 3 to 11 and Samples 18 to 19 was 0.3 ppm / K or less. Furthermore, the compressive residual stress acting on the first layers 11a and the first layers 11b was 40 MPa or less in Samples 3 to 11 and Samples 18 to 19. From this comparison, it was revealed that by having the total number of the first layers 11 and the number of the second layers 12 be 5 or more and the thickness T3 be 18 percent or more of the thickness T1, the compressive residual stress acting on the first layers 11a and the first layers 11b is further reduced, and an increase in the linear expansion coefficient in the intralayer direction due to the application of heat for brazing is suppressed.
[0114] Second embodiment A semiconductor package according to a second embodiment (hereinafter referred to as "semiconductor package 100") will be described.
[0115] Fig. 7 is an exploded perspective view of the semiconductor package 100. As shown in Fig. 7, the semiconductor package 100 includes a composite material 10, a semiconductor element 30, a case member 40, a lid 50, and terminals 60a and 60b.
[0116] The composite material 10 functions as a heat spreader in the semiconductor package 100. The semiconductor element 30 is disposed on the first surface 10a. A heat transfer member may be interposed between the semiconductor element 30 and the first surface 10a. The semiconductor element 30 becomes a heat source during operation.
[0117] The case member 40 is made of, for example, a ceramic material. The ceramic material is, for example, alumina. The case member 40 is disposed on the first surface 10a so as to surround the semiconductor element 30. The lower end (the end on the first surface 10a side) of the case member 40 is joined to the first surface 10a by, for example, brazing. The lid 50 is made of, for example, a ceramic material or a metal material. The lid 50 closes the upper end side of the case member 40.
[0118] The terminals 60a and 60b are inserted into the case member 40. As a result, one ends of the terminals 60a and 60b are located within the space defined by the first surface 10a, the case member 40, and the cover 50, and the other ends of the terminals 60a and 60b are located outside the space. b is made of, for example, a metal material, such as kovar.
[0119] Although not shown, one ends of the terminals 60a and 60b are electrically connected to the semiconductor element 30. The other ends of the terminals 60a and 60b of the semiconductor package 100 are electrically connected to a device or circuit other than the semiconductor package 100.
[0120] A heat dissipation member 70 is attached to the second surface 10b. The heat dissipation member 70 is, for example, a metal plate in which a flow path through which a refrigerant flows is formed. However, the heat dissipation member 70 is not limited to this. The heat dissipation member 70 may be, for example, a cooling fin. A heat transfer member may be interposed between the heat dissipation member 70 and the second surface 10b.
[0121] The embodiments disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is defined by the claims, not the above-described embodiments, and is intended to include all modifications within the scope and meaning equivalent to the claims. [Explanation of symbols]
[0122] 10 composite material, 10a first surface, 10b second surface, 11,11a,11b first layer, 12 second layer, 15 thin piece, 16 block, 20 laminate, 21 first plate material, 22 second plate material, 30 semiconductor element, 40 case member, 50 lid, 60a terminal, 60b terminal, 70 heat dissipation member, 80 aluminum fin, 90 heating element, 100 semiconductor package, P load, S1 preparation process, S2 heating process, S3 rolling process, T1, T2, T3 thickness.
Claims
1. A plate-shaped composite material having a first surface and a second surface opposite to the first surface, A plurality of first layers; at least one second layer; the first layer and the second layer are alternately stacked along a thickness direction of the composite material such that the first layer is located on the first surface and the second surface; the first layer is a layer containing copper, the second layer being a layer of copper-impregnated molybdenum compact; A composite material, wherein a compressive residual stress of 50 MPa or less acts on the first layer located on the first surface and the first layer located on the second surface.
2. a linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200° C. after being held at 800° C. for 15 minutes is 6 ppm / K or more and 10 ppm / K or less; 2. The composite material according to claim 1, wherein the thermal conductivity of the composite material in the thickness direction is 230 W / m·K or more after being held at 800° C. for 15 minutes.
3. the sum of the number of the first layers and the number of the second layers is 5 or more; 3. The composite material according to claim 1, wherein the thermal conductivity of the composite material in the thickness direction is 261 W / m·K or more after being held at 800° C. for 15 minutes.
4. 4. The composite material according to claim 1, wherein a linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when a temperature of the composite material is changed from room temperature to 800°C before being held at 800°C for 15 minutes is 7.5 ppm / K or more and 8.5 ppm / K or less.
5. a thickness of the first layer located on the first surface and the first layer located on the second surface is less than or equal to 25 percent of a thickness of the composite material; the thickness of the second layer is greater than 10 percent of the thickness of the composite material; a volume ratio of molybdenum in the second layer is 55 percent or more; 5. The composite material of claim 1, wherein the volume fraction of molybdenum in the composite material is greater than 13 percent and less than 43 percent.
6. a volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface is 90 percent or more; 6. The composite material of claim 1, wherein a thickness of the first layer located on the first surface and a thickness of the first layer located on the second surface are greater than or equal to 15 percent of a thickness of the composite material.
7. the thickness of the second layer is equal to or greater than 18 percent of the thickness of the composite material; 7. The composite material according to claim 1, wherein a change in linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when a temperature of the composite material is changed from room temperature to 200°C before and after holding at 800°C for 15 minutes is 0.3 ppm / K or less.
8. A plate-shaped composite material having a first surface and a second surface opposite to the first surface, A plurality of first layers; at least one second layer; the first layer and the second layer are alternately stacked along a thickness direction of the composite material such that the first layer is located on the first surface and the second surface; the first layer is a layer containing copper, the second layer being a layer of copper-impregnated molybdenum compact; a linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200° C. after being held at 800° C. for 15 minutes is 6 ppm / K or more and 10 ppm / K or less; A composite material, wherein after being held at 800°C for 15 minutes, the composite material has a thermal conductivity in the thickness direction of 230 W / m·K or more.
9. 9. The composite material according to claim 8, wherein a linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when a temperature of the composite material is changed from room temperature to 800°C before being held at 800°C for 15 minutes is 7.5 ppm / K or more and 8.5 ppm / K or less.
10. the sum of the number of the first layers and the number of the second layers is 5 or more; 10. The composite material according to claim 8, wherein the thermal conductivity of the composite material in the thickness direction is 261 W / m·K or more after being held at 800° C. for 15 minutes.
11. a thickness of the first layer located on the first surface and the first layer located on the second surface is less than or equal to 25 percent of a thickness of the composite material; the thickness of the second layer is greater than 10 percent of the thickness of the composite material; a volume ratio of molybdenum in the second layer is 55 percent or more; 11. The composite material of claim 8, wherein the volume fraction of molybdenum in the composite material is greater than 13 percent and less than 43 percent.
12. a volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface is 90 percent or more; 12. The composite material of claim 8, wherein a thickness of the first layer located on the first surface and a thickness of the first layer located on the second surface are greater than or equal to 15 percent of a thickness of the composite material.
13. the thickness of the second layer is equal to or greater than 18 percent of the thickness of the composite material; 13. The composite material according to claim 8, wherein a change in linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when a temperature of the composite material is changed from room temperature to 200°C before and after holding at 800°C for 15 minutes is 0.3 ppm / K or less.
14. A plate-shaped composite material having a first surface and a second surface opposite to the first surface; a case member brazed to either the first surface or the second surface, the composite material having a plurality of first layers and at least one second layer; the first layer and the second layer are alternately stacked along a thickness direction of the composite material such that the first layer is located on the first surface and the second surface; the first layer is a layer containing copper, the second layer being a layer of copper-impregnated molybdenum compact; a linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200° C. is 6 ppm / K or more and 10 ppm / K or less; The thermal conductivity of the composite material in the thickness direction is 230 W / m K or more; the sum of the number of the first layers and the number of the second layers is 5 or more; A semiconductor package, wherein the thermal conductivity of the composite material in the thickness direction is 261 W / m·K or more after being held at 800° C. for 15 minutes.
15. a thickness of the first layer located on the first surface and the first layer located on the second surface is less than or equal to 25 percent of a thickness of the composite material; the thickness of the second layer is greater than 10 percent of the thickness of the composite material; a volume ratio of molybdenum in the second layer is 55 percent or more; 15. The semiconductor package of claim 14, wherein a volume ratio of molybdenum in the composite material is greater than 13 percent and less than 43 percent.
16. a volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface is 90 percent or more; 16. The semiconductor package of claim 14 or 15, wherein the thickness of the first layer located on the first surface and the thickness of the first layer located on the second surface are greater than or equal to 15 percent of the thickness of the composite material.
17. A plate-shaped composite material having a first surface and a second surface opposite the first surface; a case member brazed to either the first surface or the second surface, the composite material having a plurality of first layers and at least one second layer; the first layer and the second layer are alternately stacked along a thickness direction of the composite material such that the first layer is located on the first surface and the second surface; the first layer is a layer containing copper, the second layer being a layer of copper-impregnated molybdenum compact; a linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200° C. is 6 ppm / K or more and 10 ppm / K or less; The thermal conductivity of the composite material in the thickness direction is 230 W / m K or more; the thickness of the second layer is equal to or greater than 18 percent of the thickness of the composite material; A semiconductor package, wherein a change in linear expansion coefficient of the composite material in a direction parallel to the first surface and the second surface when the temperature of the composite material is changed from room temperature to 200°C before and after holding at 800°C for 15 minutes is 0.3 ppm / K or less.
18. The thickness of the first layer located on the first surface and the first layer located on the second surface is 25 percent or less of a thickness of the composite material; the thickness of the second layer is greater than 10 percent of the thickness of the composite material; a volume ratio of molybdenum in the second layer is 55 percent or more; 20. The semiconductor package of claim 17, wherein a volume ratio of molybdenum in the composite material is greater than 13 percent and less than 43 percent.
19. A volume ratio of copper in the first layer located on the first surface and in the first layer located on the second surface is 90 percent or more; 19. The semiconductor package of claim 17 or 18, wherein a thickness of the first layer located on the first surface and a thickness of the first layer located on the second surface are greater than or equal to 15 percent of a thickness of the composite material.
Citation Information
Patent Citations
Heat radiating substrate for semiconductor device and its manufacture
JP1994268117A
Heat dissipation substrate and its manufacturing method
JP2006060247A
Manufacturing method and forming method of cladding material and radiation substrate using the same
JP2007115731A
Composite material, semiconductor-mounted heat dissipating board, and ceramic package using the same
JP2007142126A
Radiator plate and manufacturing method for the same
JP2019096654A